2020
DOI: 10.1007/s00170-020-05250-9
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the efficiency of material removal using dual laser micromachining

Abstract: A continuous wave melting laser combined with a nanosecond ejection laser has been shown to improve the material removal efficiency by a factor of 2 to 8 compared with laser ablation processes reported in the literature. The decrease in the energy required for the combined lasers is primarily due to the optimisation of the irradiation time in the melting process, which is responsible for the majority of the total energy. For the laser used in this study, the optimal interaction time corresponding to the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Upon further observation, the damaged pixels display a regular square shape, consistent with the structure formed by etching with inductively coupled plasma (ICP) to isolate the pixels and subsequent glue filling [7]. By comparing this morphology to those caused by thermal effect in other materials [12,27], it can be concluded that the bare leakage of three pixels is mainly due to stress effect. Therefore, at such laser energy density level, the damage is caused by a combination of melting and stress, with the stress being the predominant factor.…”
Section: Damage Morphology and Formation Mechanismmentioning
confidence: 67%
“…Upon further observation, the damaged pixels display a regular square shape, consistent with the structure formed by etching with inductively coupled plasma (ICP) to isolate the pixels and subsequent glue filling [7]. By comparing this morphology to those caused by thermal effect in other materials [12,27], it can be concluded that the bare leakage of three pixels is mainly due to stress effect. Therefore, at such laser energy density level, the damage is caused by a combination of melting and stress, with the stress being the predominant factor.…”
Section: Damage Morphology and Formation Mechanismmentioning
confidence: 67%
“…Further, several response characteristics like surface roughness, dross height, kerf width, kerf taper angle, and striation can be optimized. This is accomplished by carefully changing parameters such as the laser power, pulse duration, focus depth, scanning speed, cutting speed and gas pressure [38][39][40][41][42]. This equilibrium is essential for accomplishing the objective of responses and reducing the amount of time and resources.…”
Section: Significance Of Optimization Techniques Of Lbmmentioning
confidence: 99%
“…The analyses of environmental aspects of the laser cutting technology [16] and cutting process efficiency [17] have also been considered. Likewise, some specific physical process phenomena, which take place during the actual cutting process, have also been addressed by researchers including melt film characteristics on the cutting front [18], optimal laser beam configurations [19], laser beam absorption [20], multiple laser beam reflections [21], aerodynamic interactions between the workpiece material and assisting gas [22], melt flow dynamics [23], material removal efficiency [24], laser beam oscillation techniques for quality improvements [25], and temperature distribution in the cutting region [26].…”
Section: Introductionmentioning
confidence: 99%